2021
DOI: 10.3390/jcm10143113
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Pediatric Acute Kidney Injury—Are We Ready to Translate Them into Everyday Practice?

Abstract: Pediatric acute kidney injury (AKI) is a major cause of morbidity and mortality in children undergoing interventional procedures. The review summarizes current classifications of AKI and acute kidney disease (AKD), as well as systematizes the knowledge on pathophysiology of kidney injury, with a special focus on renal functional reserve and tubuloglomerular feedback. The aim of this review is also to show the state-of-the-art in methods assessing risk and prognosis by discussing the potential role of risk stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…This study assessed the predictive accuracy of uCysC at the cutoff of 1.26 mg/g uCr, and clearly showed that the uCysC at the threshold can be used to identify greater risk of AKI in critically ill children at the age of more than 1 month. As we know, defining an efficient and reliable tool for AKI assessment in children is still a challenge, because the pathophysiology of AKI in children can be affected by ongoing tubular development, greater renal reserve, and superior renal regenerative potential compared with adults [ 16 , 17 , 32 ]. Although as a sensitive biomarker for AKI and mortality [ 20 22 , 33 , 34 ], the levels of uCysC are inversely correlated with age and body weight in neonates and children [ 21 , 22 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study assessed the predictive accuracy of uCysC at the cutoff of 1.26 mg/g uCr, and clearly showed that the uCysC at the threshold can be used to identify greater risk of AKI in critically ill children at the age of more than 1 month. As we know, defining an efficient and reliable tool for AKI assessment in children is still a challenge, because the pathophysiology of AKI in children can be affected by ongoing tubular development, greater renal reserve, and superior renal regenerative potential compared with adults [ 16 , 17 , 32 ]. Although as a sensitive biomarker for AKI and mortality [ 20 22 , 33 , 34 ], the levels of uCysC are inversely correlated with age and body weight in neonates and children [ 21 , 22 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains a gap between these recommendations and the clinical application, and whether elevation in biomarkers without any changes in SCr/oliguria or a change in SCr/oliguria without any change of damage biomarker is associated with worse kidney and patient outcomes remains elusive [ 7 , 8 , 13 15 ]. This is particularly true in children, because the results obtained in adults seem difficult to be transferred directly into the pediatric field, where the results and their interpretation are age-dependent [ 16 , 17 ]. The incidence and outcome of AKI substages in critically ill children remain however largely unknown, and whether detecting AKI substages would be relevant with respect to outcome is needed to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The major causative factors for CKD were congenital anomalies of the kidney and urinary tract (CAKUT) (45 children), including reflux nephropathy (19 cases), obstructive uropathy (14 patients), and hypo/dysplastic kidneys (12). Other underlying diseases were: chronic glomerulonephritis (10), polycystic kidney disease (4), and hemolytic uremic syndrome (2). CAKUT was the only cause of CKD in CKD I and the dominant cause in CKD II (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The regenerative potential of renal tubules is clearly seen in the course of acute tubular necrosis, when the increased fractional excretion of sodium results from the timely dysfunction of proximal tubules and allows sequential control until its normalization preceding recovery. The working hypothesis is that similar follow-up of tubular reabsorption capacity is available in the course of chronic kidney disease (CKD) and that it is possible to define a breakthrough point at which reversal of tubular dysfunction is no longer possible [ 2 ]. The breakthrough is usually preceded by compensatory mechanisms aimed at maintaining the status quo.…”
Section: Introductionmentioning
confidence: 99%
“…Гіпотеза Бреннера описує гемодинамічні механізми, спрямовані на підтримку екскреторної здатності нирок: нефронний дефіцит підвищує ШКФ кожного окремого нефрону. Ці адаптаційні гемодинамічні зміни спричиняють внутрішньоклубочкову гіпертензію, гломерулярну та тубулярну гіпертрофію, що на фоні редукованої кількості нефронів призводить до розвитку вогнищевого сегментарного гломерулосклерозу, особливо у ПНД з НМТ [43].…”
Section: патофізіологія та патоморфологія ураження нирокunclassified